In vitro assessment of cytotoxic activities of Lachesis muta muta snake venom. - Stephanie Stransky; Fernanda Costal-Oliveira; Letícia Lopes-; Clara Guerra-Duarte; Carlos Chávez-Olórtegui; Vania Maria Martin Braga (Public Library of Science (PLoS), 2018)
Envenomation by the bushmaster snake Lachesis muta muta is considered severe, characterized by local effects including necrosis, the main cause of permanent disability. However, cellular mechanisms related to cell death and tissue destruction, triggered by snake venoms, are poorly explored. The purpose of this study was to investigate the cytotoxic effect caused by L. m. muta venom in normal human keratinocytes and to identify the cellular processes involved in in cellulo envenomation. In order to investigate venom effect on different cell types, Alamar Blue assay was performed to quantify levels of cellular metabolism as a readout of cell viability. Apoptosis, necrosis and changes in mitochondrial membrane potential were evaluated by flow cytometry, while induction of autophagy was assessed by expression of GFP-LC3 and analyzed using fluorescence microscopy. The cytotoxic potential of the venom is shown by reduced cell viability in a concentration-dependent manner. It was also observed the sequential appearance of cells undergoing autophagy (by 6 hours), apoptosis and necrosis (12 and 24 hours). Morphologically, incubation with L. m. muta venom led to a significant cellular retraction and formation of cellular aggregates. These results indicate that L. m. muta venom is cytotoxic to normal human keratinocytes and other cell lines, and this toxicity involves the integration of distinct modes of cell death. Autophagy as a cell death mechanism, in addition to apoptosis and necrosis, can help to unravel cellular pathways and mechanisms triggered by the venom. Understanding the mechanisms that underlie cellular damage and tissue destruction will be useful in the development of alternative therapies against snakebites.